Efecto de Zingiber officinale “kión” en el control de parasitosis causadas por Monogenoideos (monogenoidea) en alevinos de Colossoma macropomum (cuvier, 1816) “gamitana” y Piaractus brachypomus (cuvier,1818) “paco” - Pasquel Pinedo, Carmen Patricia (2023)
The present research was carried out between June and December 2022, and its objective was to evaluate the effect of aqueous extract of Zingiber officinale in the control of parasitosis in Colossoma macropomum and Piaractus brachypomus fry. A total of 268 fry were collected and conditioned in the laboratory of Parasitology and Aquaculture Health at the Peruvian Amazon Research Center - IIAP. For its antiparasitic effect, the efficacy of concentrations of 0, 25, 50 and 75 mg/ml of aqueous extract was tested in in vitro tests and tolerance in in vivo tests with 30-minute baths. The results of the study showed that the highest percentage of efficacy was in treatment 3 (75 mg/ml) in Colossoma macropomum with 89.55% effectiveness and Piaractus brachypomus with 90.72% effectiveness. In relation to the parasite load was reduced to 90% for Colossoma macropomum and 80% for Piaractus brachypomus after exposure to the aqueous extract of Zingiber officinale, also, the tolerance tests in Colossoma macropomum the LC50 was 78.57 mg/ml and in Piaractus brachypomus it was 79.17 mg/ml. On the other hand, it was determined that the aqueous extract does not alter the physical and chemical parameters of the water and they are maintained in acceptable ranges for the species under study. It is concluded that the phytotherapeutic used to control parasitosis in Colossoma macropomum and Piaractus brachypomus shows an antiparasitic effect, which is attributed to the exposure time and concentration of the producto.